D. G. Leahy and the Thinking Now Occurring. - McCullough, Lissa; Wolfson, Elliot R. (Albany : State University of New York Press, 2021)
A critical introduction to the American philosopher D. G. Leahy (1937-2014), whose oeuvre sets forth a fundamental thinking in which change itself is revealed to be the very essence of reality and mind.
Introduction to D.G. Leahy : a quick start guide for the vexted and perplexed / Lissa McCullough -- Part I. History and time. History and the thinking now occurring / Charles Stein -- Temporal diremption and the novelty of genuine repetition / Elliot R. Wolfson -- A metaphysics of enchantment or a case of immanentizing the Eschaton? / Graham James McAleer -- Part II. Apocalyptic actuality. Apocalypticism im modern thinking : Descartes, Hegel, Leahy / Thomas J.J. Altizer -- The shape of Catholic Apocalypse / Cyril O'Regan -- the act of omnipotence : abolition of the mystical quest / Michael James Dise -- Part III. A physical ethics. The ethics of simplicity / Nathan Tierney -- The vanishment of evil from the world / Todd Carter -- the transparancy of the Good / Alina N. Feld -- Part IV. The edge where creating begins. Concerning the absolute edge / Edward S. Casey -- To thinking the beginning : the apocalyptic "I" / Sarah Lilly Eaton -- Life at the edge : medicine and the new thinking / Steven B. Hoath, MD.
eBooks on EBSCOhost
Keywords: Leahy, D. G. -- 1937-; Philosophy; Philosophie; philosophy; Philosophy; Electronic books